Interpretation and back-analysis of the damage observed in a deep tunnel after the 2016 Norcia earthquake in Italy. (July 2019) - Callisto, Luigi; Ricci, Cecilia
Highlights: A roadway tunnel was damaged by the Norcia Earthquake, in Italy. A back-analysis of the damage was carried out with an original methodology. The analysis was based on the available seismic records of the same event. The damage was principally caused by seismic load acting on a lining with a reduced thickness. The dynamic response of the lining contributed substantially to the observed damage. Abstract: This paper deals with the interpretation of the damage originated by the 2016 Norcia earthquake, Italy, in a deep tunnel excavated in a calcareous rock mass. A careful investigation of the damage pattern, together with the availability of seismic signals recorded in the vicinity of the tunnel during the earthquake, prompted a back-analysis of the observed phenomenon. The study hinged on a combination of site response analyses, simulation of the tunnel construction, and computation of the effect of the earthquake on the tunnel lining. Specifically, the damage caused by the earthquake in the tunnel lining was evaluated both with a decoupled procedure, based on equivalent static loading, and with a fully coupled dynamic analysis of the soil-structure interaction. The results obtained from the back-analysis were in a good agreement with the observations, and contributed to evidence the main causes of the damage, related to the specific geometry and to the dynamic response of the lining. The approach used in the paper, validated for the present case study through the comparison with the observed tunnel damage, may be useful to assess the seismic vulnerability of existing tunnels and for the seismic design of new underground structures.